Pengembangan Aplikasi Mobile Berbasis Z-score untuk Deteksi Dini dan Pemantauan Status Gizi Balita Menggunakan Standar Antropometri WHO - Huda, Irkhamul Gustia; Wulandari, Sri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Stunting remains a critical public health problem in Indonesia, with a national prevalence of 19.8% reported in 2024, emphasizing the need for accurate and accessible nutrition monitoring tools that can be utilized independently by parents at home. This study developed a mobile application called “Gizi Pantau,” which applies the WHO-standardized Z-score method to assess toddler nutritional status through three key anthropometric indicators, namely Weight-for-Age, Height/Length-for-Age, and Weight-for-Height/Length. The purpose of this research is to improve the practicality and continuity of nutrition monitoring through mobile health technology. The system development followed the SDLC Waterfall model, covering requirement analysis, system design, implementation using Flutter and Firebase, and system testing. Evaluation was conducted using Black Box Testing, which resulted in a 100% success rate across five functional test scenarios, accuracy validation using 20 toddler data samples with 98.3% accuracy and an average deviation of ±0.03 SD compared to manual WHO-based calculations, and acceptability testing involving 20 parents and 7 healthcare professionals yielding an average score of 4.50 categorized as Very Good. These results indicate that Gizi Pantau is feasible and effective as an early detection and continuous nutrition monitoring tool, supporting Indonesia’s national stunting reduction efforts.